2009
DOI: 10.3233/ies-2009-0337
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between isokinetic strength of knee extensors/flexors, jumping and anaerobic performance

Abstract: The purpose of this study was to investigate the relationship between isokinetic strength of knee, vertical jump and anaerobic peak power. Twenty one healthy young male voluntarily participated in this study. Squat Jump (SJ), Counter Movement Jump (CMJ) and Wingate anaerobic power test were performed. Bilateral concentric isokinetic strength of the knee extensors/flexors was evaluated at 60, 120 and 180 • /s. CMJ height had a significant and moderate relationship with the isokinetic knee strength of extension … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Quadriceps strength was measured during isometric, concentric, and eccentric contraction at slow (60°/s) and fast (180°/s) velocities. These velocities of contraction during isokinetic testing are associated with functional performance (e.g., hopping, jumping) [ 31 , 32 ]. Quadriceps strength was measured before and after FKJC (immediately, 20, and 40 min after) to examine the change in quadriceps strength over time.…”
Section: Methodsmentioning
confidence: 99%
“…Quadriceps strength was measured during isometric, concentric, and eccentric contraction at slow (60°/s) and fast (180°/s) velocities. These velocities of contraction during isokinetic testing are associated with functional performance (e.g., hopping, jumping) [ 31 , 32 ]. Quadriceps strength was measured before and after FKJC (immediately, 20, and 40 min after) to examine the change in quadriceps strength over time.…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have examined the relationship between the ability ff walking sprint and muscle strength (Moirenfeld et al, 2000). From the research results, the relationship between muscle strength and vertical jump performance (CMJ and SJ) was found by different authors (Atabek et al, 2009;Paasuke M, Ereline J, 2001;Tsiokanos et al, 2002). Furthermore, (Tharp et al, 1985) found a significantly strong correlation between isokinetic knee strength and the strength and anaerobic capacity of female runners and female middle-distance runners.…”
Section: Discussionmentioning
confidence: 97%
“…There are even authors whose results show the absence of correlation between PT and CMJ. For example, (Atabek & Sönmez, 2009;Blackburn & Morrissey, 1998;Kovačević, Abazović, Bradić, & Vrcić, 2012), reported statistically insignificant correlation coefficients between these variables.…”
Section: Discussionmentioning
confidence: 99%